Interferences between the ecological network and urbanized areas in Poland - Zwierzchowska, Iwona (Acta Geographica Debrecina Landscape & Environment series, 2008)
This paper presents spatial relations between Polish urban areas and valuable habitats and links between them composing the country’s ecological network. The quantitative analysis for 891 towns and cities was conducted using GIS techniques based on cartographic vector data and statistical data. Valuable habitats and links between them, such as national parks, landscape parks, CORINE biotopes sites, wildlife corridors linking NATURA 2000 sites and ECONET areas, can be found in 72% of Polish towns and cities. The proportion of artificial surfaces in those areas is different depending on the size of a town or city and its location. Urban areas with the highest index of presence of valuable habitats and links between them are concentrated in the south of Poland, where settlement network is most dense. However, in the case of those areas the proportion of artificial surfaces interfering with the ecological network is lower than Poland’s average, being 16%. The pressure of anthropogenic land cover extending onto the country’s ecological network is most conspicuous in urban areas with a population of at least several dozen thousand residents where the average developed area is 20.8% of their total area. The danger for the continuity of the nature system is best seen in the north western Poland, where artificial surfaces interference in towns and cities is largest. The analysis performed identified 82 towns and cities, in which the preservation of the continuity of the ecological network should be a priority in spatial management because of a higher than average index of the presence of valuable habitats and links between them and large proportion of artificial surfaces in those areas.